IMPLEMENTATION OF MURDER TYPE COOPERATIVE LEARNING MODEL IN BIOLOGY LEARNING - Yaumil Istiqlal M.Nur; Devi Syafrianti; Nulda Azmi (Biotik, 2021)
The purpose of this study was to determine the learning outcomes of students by applying the MURDER type cooperative learning model at MTsN Sijunjung. This type of research is a quasi-experimental research with a randomized control group design post-test only design. The instrument used was a test of learning outcomes, by compiling tests, validation tests, trials, and item analysis. Data analysis techniques are the normality tests, homogeneity tests, and hypothesis tests. The results showed differences in the average value, standard deviation, and variance of the experimental class and the control class. The results showed that the research hypothesis was accepted. In conclusion, the learning outcomes in the experimental class with the MURDER type cooperative learning model are better than the control class (normal).